2019
DOI: 10.1002/slct.201804069
|View full text |Cite
|
Sign up to set email alerts
|

Base Promoted Tandem Cyclization ofo‐Phenylenediamine with Ninhydrin‐phenol Adducts: An Unprecedented Route to Phenol Appended Isoindolo[2,1‐a]quinoxaline Fluorophore

Abstract: Synthesis of fluorescent molecules has drawn considerable attention due to their potential applications in life and material sciences. Here we report a metal‐free approach to a new class of fluorophore, namely, 6‐(2‐hydroxyaryl)isoindolo[2,1‐a]quinoxalin‐11(5H)‐ones exploiting ninhydrin ring system via base promoted tandem cyclization. The readily obtainable phenolic adducts of ninhydrin undergoes smooth reaction with o‐phenylenediamine in refluxing ethylene glycol/Et3N via breaking of C−C bond, N‐insertion, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 65 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…A metal-free tandem cyclization approach to access other fused quinoxalines, namely isoindolo[2,1- a ]quinoxalines 127 has been demonstrated by Das et al , in 2019 ( Scheme 37 ). 117 To find out the optimum condition, the reaction of ninhydrin 126 bearing phenolic adducts, with o -phenylenediamine 35 was initially performed in the presence of different bases including Et 3 N, piperazine, pyridine, Et 2 NH, and solvent system like ethylene glycol, water, MeOH, EtOH, glycerol. From these experiments, it was concluded that the utilization of Et 3 N in ethylene glycol provides easy access to the products within a very short reaction time.…”
Section: Synthesis Of Fused Quinoxalines Based On Metal-free Two-comp...mentioning
confidence: 99%
See 1 more Smart Citation
“…A metal-free tandem cyclization approach to access other fused quinoxalines, namely isoindolo[2,1- a ]quinoxalines 127 has been demonstrated by Das et al , in 2019 ( Scheme 37 ). 117 To find out the optimum condition, the reaction of ninhydrin 126 bearing phenolic adducts, with o -phenylenediamine 35 was initially performed in the presence of different bases including Et 3 N, piperazine, pyridine, Et 2 NH, and solvent system like ethylene glycol, water, MeOH, EtOH, glycerol. From these experiments, it was concluded that the utilization of Et 3 N in ethylene glycol provides easy access to the products within a very short reaction time.…”
Section: Synthesis Of Fused Quinoxalines Based On Metal-free Two-comp...mentioning
confidence: 99%
“…Consequently, the intramolecular cyclization of (Int-30), followed by elimination of water leads to the final products 127 ( Scheme 37 ). 117 …”
Section: Synthesis Of Fused Quinoxalines Based On Metal-free Two-comp...mentioning
confidence: 99%
“…Donepezil (AChE inhibitor) is an approved drug for the treatment of Alzheimer's disease [8] . Moreover, substituted 1‐indanones are also served as indispensable intermediates for the synthesis of diverse organic scaffolds including heterocycles [9–13] . There are so many reports where indanone analogues are successfully employed as chiral ligands in asymmetric synthesis [14] and metal‐ligands for the preparation of metal complexes [15] .…”
Section: Introductionmentioning
confidence: 99%
“…26 Recently, we employed monoarylated ninhydrin-adducts to develop a new uorophore system. 27,28 Some indanone-based uorophores were also explored to act as a receptor for specic metal ions. 29,30 Ninhydrin is basically an indanone class compound, and indanone core structures have been found in numerous natural products (Fig.…”
Section: Introductionmentioning
confidence: 99%